The trouble with Jessica [videorecording (DVD)] - Winn, Matt; Winn, Matt; Handel, James; Henderson, Shirley, 1965-; Sewell, Rufus, 1967-; Williams, Olivia, 1968-; Varma, Indira; Tudyk, Alan; Oliver, Tristan; Cooper, Matt (Musician); Elum-Baldrés, Bárbara (Music Box Films, 2025)
Married couple Sarah and Tom are in terrible financial trouble. On the brink of losing everything, they've managed to find a buyer for their stylish London home. When their best friends Richard and Beth come over for a final dinner, an uninvited old friend, Jessica, tags along. After a seemingly trivial argument at dinner, Jessica disappears. She has the temerity to hang herself in the garden, totally oblivious to the adverse consequences for Sarah and Tom's real estate sale. The only solution: Sarah and Tom must convince Richard and Beth to help take care of this little inconvenience. If they're clever enough about it, what could possibly go wrong?